An exploratory study on the prevalence of early dementia among geriatric population in a rural area of district Jammu - Sahni, Bhavna; Dewan, Deepika; Kumar, Dinesh; Bala, Kiran (International Journal Of Community Medicine And Public Health, 2017)
Background: Dementia is one of the major causes of disability and dependency among older people worldwide. Dementia can no longer be neglected but should be considered as a public health priority especially by those who are involved in framing and implementing various health policies and programmes. Community based screening to detect dementia in undiagnosed individuals is emerging as a promising health promotion strategy. Methods: The present study was an exploratory cross sectional community based study, conducted in rural area of Jammu region in the month of July and August 2016 among all individual aged 60 years or more who were willing to participate in the study. A brief informant-based screening questionnaire, namely the Symptoms of Early Dementia-11 Questionnaire (SED-11Q) for screening of early dementia was used. Results: A total of 129 individuals participated in the study and out of them 18 persons were categorised to be suffering from early dementia using SED-11Q with overall prevalence rate of 13.95%. Dementia was more common among females as compared to males and prevalence of dementia was highest among people belonging to lowermiddle and middle socioeconomic classes. Conclusions: The SED-11Q categorised nearly 13.95% asymptomatic individuals to be suffering from dementia which is an alarming figure considering it as a disease which affects quality of life and contributes to morbidity of affected individuals.